Low Multiplication Value of Absolute Monocyte Count and Absolute Lymphocyte Count at Diagnosis May Predict Poor Prognosis in Neuroblastoma - Tamura, Akihiro; Inoue, Shotaro; Mori, Takeshi; Noguchi, Jun; Nakamura, Sayaka; Saito, Atsuro; Kozaki, Aiko; Ishida, Toshiaki; Sadaoka, Kay; Hasegawa, Daiichiro; Kosaka, Yoshiyuki; Miyanishi, Masanori (Frontiers in Oncology, 2020)
Despite the growing evidences that immune dysfunction contribute to tumor progression, the prognostic value in patients with neuroblastoma regarding circulating immune blood cell counts has not been well characterized. To answer this, we conducted a retrospective study to evaluate the prognostic value of the circulating immune cell counts at diagnosis in a cohort of 55 patients with neuroblastoma. Based on a novel index by multiplying the absolute monocyte count (AMC) /μl and absolute lymphocyte count (ALC) /μl, we sub-grouped patients with AMC × ALC ≥ 1 × 106 (/μl)2 as high group and patients with AMC × ALC < 1 × 106 (/μl)2 as low group. In the entire cohort, the 4-year progression-free survival (PFS) and overall survival (OS) for high group (n = 38) vs low group (n = 17) was 81.7% (95%CI; 63.6%–91.3%) and 90.7% (95%CI; 73.8%–96.9%) vs 31.7% (11.6%–54.1%) and 56.5% (29.7%–76.4%) (p < 0.001 for PFS and p = 0.015 for OS) respectively, suggesting that a low AMC × ALC is associated with poor prognosis. In the subgroup analysis for high-risk patients, the 4-year PFS and OS for high group (n = 17) vs low group (n = 13) was 59.8% (31.2%–79.7%) and 79.8% (49.4%–93.0%) vs 8.5% (0.5%–31.7%) and 42.0% (15.4%–66.8%) (p < 0.001 for PFS and p = 0.089 for OS), respectively. Our data demonstrate that AMC × ALC at diagnosis is a cost-effective and easily measurable biomarker for predicting prognosis in neuroblastoma.